(untitled) (Al-Qamar, 2023)
Augmented reality (AR) can enhance the physical world by adding digital information a computer generates in real-time. The ability to provide (virtual) goods creates exciting opportunities for users to interact with the company and its products. Although the market for augmented reality technology is predicted to grow exponentially by the year 2030, and many businesses have already tried to use the technology to expand their operations, it is unclear whether AR can improve consumers’ shopping habits and produce positive results like increased behavioural intentions to use augmented reality apps. This paper employs an experimental methodology to ascertain the causal effect of several AR applications on the University of the Punjab Institute of Business Administration students to fill the research gap statistically. Executive students have been selected as a suitable sample to uncover influences on behavioural intentions experimentally. Lastly, the retail-focused AR application is believed to affect behavioural intentions through high augmentation and interactivity, leading users to purchase AR apps. However, technostress was not a significant driver, having an insignificant mediating effect between augmentation, interactivity, and behavioural intention to use AR applications.